Programming in C++ - Dewhurst, Stephen C.; Stark, Kathy T. (New Jersey : Prentice-Hall, 1989)
This book has benefited by contributions made by many of those who participated in the development of C++.
Chapter 0. Introduction -- Chapter 1. Data types and operations -- Chapter 2. Procedural programming -- Chapter 3. Classes -- Chapter 4. Data abstraction -- Chapter 5. Inheritance -- Chapter 6. Object-oriented programming -- Chapter 7. Storage management -- Chapter 8. Libraries.
Includes bibliographical references and index.
Keywords: C++ (COMPUTER PROGRAM LANGUAGE)